GIGVAGANZA 2 in the house! - Ezihaslinda, Ngah (Pusat Bahasa Moden dan Sains Kemanusiaan, 2012)
17 July 2012. A total of 318 UMP diploma students participated in GIGVAGANZA 2 as part of their overall assessments for UHL 1412(Foundation English). This time, they were also joined by school students from around Kuantan area. There were four participating schools who had gladly accepted our invitations, they were SMK Sultanah Hajjah Kalsom, SM Sains Sultan Haji Ahmad Shah Pekan, SMK Sri Pekan and SMK Gambang.